Percepción de los texcocanos sobre su patrimonio arqueológico: caso cerro de Tetzcotzinco - Durán-Méndez, Jorge Antonio; Almeraya-Quintero, Silvia Xóchilt; Rosas-Jaco, María Isabel; Guajardo-Hernández, Lenin G.; Borja-Bravo, Mercedes (Revista Mexicana de Ciencias Agrícolas, 2026)
Perception studies are very useful when seeking to generate information through the population perspective on a specific topic; this data collection process also contributes to managing the various elements that constitute the territorial space, such as archaeological heritage, which is believed to influence the reinforcement of the historical and cultural identity of the population; the objective of the study was to generate information about the perception of the Tetzcotzinco Archaeological Zone among the population of Texcoco, with the purpose of providing data that contribute to the design of strategies for its preservation and use; the methodology employed was based on activities such as documentary review, field visits, and preparation of semi-structured surveys and interviews with key informants; the results obtained showed a diversity of opinions about the current state of the Tetzcotzinco Archaeological Zone, as well as variability of references regarding it; it was concluded that the information generated can favor development and territorial management initiatives from which local tourism, tourism education, and the dissemination of information on the history and archaeological heritage of Texcoco are encouraged.
Keywords: desarrollo territorial; gestión territorial; identidad cultural; turismo educativo